2012
DOI: 10.1149/1.4705486
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Channel Wettability on Two-Phase Flow and Polymer Electrolyte Membrane Fuel Cell Performance

Abstract: Water management is one of the critical issues affecting polymer electrolyte membrane fuel cell (PEMFC) performance, durability and cost. Modifying the surface wettability of flow field channels in PEMFC can improve the water management and consequently the fuel cell performance. In the present work, an ex-situ investigation of the effects of channels with different surface wettability on the two phase-flow characteristics has been conducted. Horizontal graphite channel (slightly hydrophobic) and other four ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Water droplet transport on the channel surface is observed to have an elliptic spreading shape (or elliptic contact line) on the surface with a continuous change in the local contact angle (from the advancing to the receding angles) from the leading to the trailing edge of the water droplet . The elliptic water spreading shape on the surface, as shown in Figure , can be described by {x=a0.25emcos()φy=b0.25emsin()φ0.25em()πφ<π …”
Section: Model Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Water droplet transport on the channel surface is observed to have an elliptic spreading shape (or elliptic contact line) on the surface with a continuous change in the local contact angle (from the advancing to the receding angles) from the leading to the trailing edge of the water droplet . The elliptic water spreading shape on the surface, as shown in Figure , can be described by {x=a0.25emcos()φy=b0.25emsin()φ0.25em()πφ<π …”
Section: Model Formulationmentioning
confidence: 99%
“…It was found that easier water movement on the surface was obtained as the size of the silica particle in the coating material was increased, although the static contact angles measured on the solid surface with different coatings were almost the same. Therefore, sliding angle is another parameter for the description of the surface dynamic wettability associated with the water transport on the surface . As shown in Figure B, the sliding angle is normally measured as the angle of the surface inclination at which liquid starts to slide on the surface under gravity, and it represents relative easiness of a liquid droplet moving on a surface under a driving force.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the wave-like fluctuation of the water droplet shape (or height along z direction) can also be explained by the asymmetric air velocity or air shear force acting on the water droplet. Under such a kind of air shear force, water droplet can even roll on the hydrophobic surface, which has been observed in the experimental study [32]. In order to better clarify the advantage of the improved model, simulations are also carried out with the no-slip boundary condition for comparisons.…”
Section: Resultsmentioning
confidence: 91%
“…Owejan et al [144] demonstrated that a hydrophobic coating on flow field channels were retaining a higher amount of liquid water. However, Al Shakhshir et al [145] found out that despite the fact that both hydrophobic or hydrophilic treatment was reducing the overall pressure drop, the cell voltage with a parallel flow field and hydrophilic channels was more stable than that of the untreated channel, and that the hydrophobic treatment was decreasing the cell performance. The advantages of hydrophilic channels were shown by Lu et al [146], where it was found that more uniform water and gas flow distribution and a more desirable film flow regime was achieved by hydrophilically coated gas channels.…”
Section: Future Work and Perspectivesmentioning
confidence: 99%